Bio-Based Graphene Sheet/Copolymer Composite as Supporting Material for Nanocatalysts towards Electrochemical Studies and Direct Alkaline Alcohol Fuel Cells. (6th January 2022) - Selvaraj, V.; ThamilMagal, R.; Andal, V.; Arunkumar, K.; Murugan, Sivaraj
Abstract : In this work, graphene carbon sheets (BGS) were prepared from writing paper and lemon peel, and its polymer composite has a higher surface area compared with the existing Vulcan carbon. Further, the use of lead as a promoter for the oxidation of alcohol and CO on platinum-supported poly(amine-terminated cyclophosphazene-co-cyclophosphazene)-biobased graphene sheet (Poly(AFCP-co-CP)-BGS) composite was demonstrated. The size, phase morphology, and distribution of metal nanoparticles on Poly(AFCP-co-CP)-BGS composite as well as the formation of composite based catalysts were confirmed from TEM, XRD, and FTIR studies. The catalytic activity and stability of the prepared catalysts were tested and compared to methanol, ethylene glycol, glycerol, and CO in 0.5 M KOH solution. The results conclude that the lead-doped Pt/Poly(AFCP-co-CP)-BGS catalyst shows higher oxidation current with respect to onset potential and lower I f / I r ratio for alcohol as well as CO oxidation. In addition, Pt-Pb/Poly(AFCP-co-CP)-BGS catalyst was checked for direct alkaline fuel cells and proved as a potent anode catalyst in alkaline medium for real-time fuel battery applications. In addition, Poly(AFCP-co-CP)-BGS composite also promotes the catalytic reaction compared to Poly(AFCP-co-CP) and BGS supports as noticed from methanol oxidation in alkaline medium. The surface area of the prepared supporting material is 750.72 m 2 g -1, which is higher than the activated carbon (250.12m 2 g -1 ). So, the prepared Poly(AFCP-co-CP)-BGS composite is a potent support for metal deposition, electrooxidation, and single stack fuel cell constructions.